Emotional Intelligence And Leadersidp Effectiveness Of Managers In Manufacturing Firms - Beh, Hock Yau (2003)
The purpose of this study was to investigate the relationship between Emotional Intelligence and leadership effectiveness of managers in manufacturing firms. This study also examined the mediating effect of Effective Leadership Practices on the relationship between Emotional Intelligence and leadership effectiveness. Data were collected from a random sample of 181 employees in manufacturing firms located at Bayan Lepas, Kulim, Perai, Shah Alam and Ulu Klang.